KENDALI LQR DISKRIT PADA SISTEM PERGUDANGAN DENGAN KEBIJAKAN PENINJAUAN BERKALA - , DITA ANIES MUNAWWAROH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discuss about inventory control with periodic review policy. Inventory system is developed using optimal control linear quadratic regulator in discrete time. This optimal control has quadratic equation for objective function and linear equation for the constraint. This control can be used to optimize order, and the inventory so that lost sales and back order are not permitted. This research discuss inventory control with single supplier and multi-supplier. The numerical simulation indicates that the two cases of inventory control will produce an optimal order quantity, and consumer demand is always met. Keyword : linear quadratic control, inventory control, periodic review policy, single supplier and multi-supplier